Use of pasteurised human donor milk across neonatal networks in England. (March 2018) - Battersby, C.; Marciano Alves Mousinho, R.; Longford, N.; Modi, N.
Abstract: Objectives: To describe the use of pasteurised human donor milk (pHDM) in England and the influence of a human milk bank in the network. Design: Prospective observational study Setting: All 163 neonatal units (23 networks) in England 2012–2013. Patients: Preterm infants born at <32 weeks gestational age (GA). Main outcome measures: Proportion of infants and care-days fed pHDM during the first 30 postnatal days by network Methods: We extracted daily patient-level data from the National Neonatal Research Database (NNRD). We fitted a logistic regression of pHDM exposure on the presence of a pHDM bank within the network, with GA, BW z score and network as covariates. Significance was assessed by the likelihood ratio (chi-squared) test. Results: Data for 13, 463 infants were included in the study. Across the networks, the proportion (95%CI) of infants ranged from 2.0% (1.0, 3.0) to 61.0% (57.4%, 64.6%), and the proportion of care-days in which pHDM was fed from 0.08% (0.04%, 0.10%) to 21.9% (19.9%, 24.0%). In three networks <5%, and in seven networks >30% of infants received any pHDM. Variation in the use of pHDM across networks remained significant after adjustment for presence of a human milk bank within the network and all covariates ( p  < 0.001). Conclusions: Wide variation of pHDM use in England is not fully explained by presence of a pHDM bank or patient characteristics. This suggests clinical uncertainty about the use of pHDM. Highlights: What is already known on this topic? Human milk banks are increasing worldwide without strong evidence of benefit. What this study adds? Analysis of patient-level data shows wide variation in pHDM use across England, which is not fully explained by patient characteristics or presence of a human milk bank. These observations indicate uncertainty in clinical practice and provide justification for an objective evaluation of the role of pHDM in neonatal care.